Respuesta :
Answer: 7^11
Explanation:
The rule is
a^b*a^c = a^(b+c)
Note how each base is the same (both 'a' each time). The rule wouldnt work if the bases were different.
So,
a^b*a^c = a^(b+c)
7^6 * 7^5 = 7^(6+5)
7^6 * 7^5 = 7^11
In short, you just add the exponents.
Keep in mind that the base stays at 7 the whole time. It might be tempting to do 7*7 = 49, but that would be incorrect.
Answer:
=8.310133e+125
Step-by-step explanation:
Given that:
= 7^6 ⋅ 7^5. 49^11 49^35 7^11 7^35
By making all bases same (equal to 7)
= 7^6 ⋅ 7^5. 7^2*11. 7^2*35. 7^11 7^35
=7^6 ⋅ 7^5. 7^22. 7^70. 7^11 7^35
As bases are same so powers will be added
=7^6+5+22+ 70+11+35
=7^149
=8.310133e+125
i hope it will help you!